Non-Suicidal Self-Injury Elevates Suicide Risk among United States Military Personnel with Lifetime Attempted Suicide. Issue 3 (3rd July 2018) - Baer, Margaret M.; LaCroix, Jessica M.; Browne, Joy C.; Hassen, Helena O.; Perera, Kanchana U.; Weaver, Jennifer; Soumoff, Alyssa; Ghahramanlou-Holloway, Marjan
Abstract : Military psychiatric inpatients with and without a lifetime history of non-suicidal self-injury (NSSI), combined with a history of at least one suicide attempt, were compared on suicide ideation severity, number of suicide attempts, and Interpersonal-Psychological Theory of Suicide variables. Data were derived from baseline assessments performed in a psychotherapy randomized controlled trial. Lifetime history of NSSI and lifetime number of suicide attempts were assessed using the Columbia Suicide Severity Rating Scale (C-SSRS; Posner et al., 2011 ). Individuals with versus without a combined lifetime history of attempted suicide and NSSI showed significant elevations on thwarted belongingness and acquired capability for suicide. No significant between-group differences were found on perceived burdensomeness, frequency, duration, and controllability of suicide ideation, or number of lifetime suicide attempts. A history of NSSI, above and beyond attempted suicide, appears to increase service members' social alienation and acquired capability for suicide.